Enzymatic catalysis for sustainable production of high omega‐3 triglyceride oil using imidazolium‐based ionic liquids. Issue 8 (6th August 2018) - Fu, Hong; Li, Mengqi; Ni, Ruimin; Lo, Yangming Martin
Abstract: Two different fish oil preparations, namely triglycerides and ethyl esters containing, respectively, 30.02% and 74.38% of omega‐3 fatty acids, were employed as the substrates for transesterification. Catalyzed by immobilized lipase using imidazolium‐based ionic liquid systems, the total content of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the resulting triglyceride reached 63.60% when 4% hydrophobic ionic liquid was used, which was 11.74% higher than that of the triglyceride produced in a solvent‐free reaction system. The activation energy of the product (triglyceride‐type fish oil) was 173.64 KJ mol −1, which was not significantly different from that of the commercial ethyl ester‐type fish oil, so were the other thermal oxidative kinetic parameters. The kinetic parameters depicting the thermal and oxidative stability of the fish oil product provide the basis for industrial processing, storage, and applications. Abstract : Catalyzed by immobilized lipase using imidazolium‐based ionic liquid systems, the total content of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the resulting triglyceride reached 63.60% when 4% hydrophobic ionic liquid was used, which was 11.74% higher than that of the triglyceride produced in a solvent‐free reaction system. The activation energy of the product was not significantly different from that of the commercial ethyl ester‐type fish oil, so were the other thermal oxidative kinetic parameters. The kinetic parameters depicting the thermal and oxidative stability of the fish oil product provide the basis for industrial processing, storage, and applications.